Follicular Lymphoma Presenting with Leptomeningeal Disease - Costa, Rubens; Costa, Ricardo; Costa, Renata (Case Reports in Hematology, 2014)
Follicular lymphoma is generally an indolent B cell lymphoproliferative disorder of transformed follicular center B cells. Central nervous system metastasis is a very rare complication portending a very poor prognosis. We report a rare case of follicular lymphoma presenting with leptomeningeal involvement achieving a complete remission after initial therapy.